The impact of COVID-19 on the supply chain disruption of Micro and small companies in the confection sector in Metropolitan Lima during 2020 and 2021 - Quiñones Gavilan, Diana Elva (2023)
This research will seek the relationship between the effect of COVID-19 and the supply chain's disruption, delimiting the target population as the citizens of Metropolitan Lima. We will work with a sample of 100 surveys to workers who meet the requirement of 3 years working in the confection sector. The data collected will be processed and examined using Minitab Version 20.3, so the reliability and validity of the data obtained will be reviewed. Based on the results, a correlation between the dimensions of cost, sales and production in the supply chain and the severity of COVID-19 was observed, a statement supported numerically. The results of the research show how much a health phenomenon can directly impact a supply chain causing a disruption in small and micro confection companies.